2014
DOI: 10.1109/tbme.2014.2311387
|View full text |Cite
|
Sign up to set email alerts
|

Automated Grouping of Action Potentials of Human Embryonic Stem Cell-Derived Cardiomyocytes

Abstract: Methods for obtaining cardiomyocytes from human embryonic stem cells (hESCs) are improving at a significant rate. However, the characterization of these cardiomyocytes is evolving at a relatively slower rate. In particular, there is still uncertainty in classifying the phenotype (ventricular-like, atrial-like, nodal-like, etc.) of an hESC-derived cardiomyocyte (hESC-CM). While previous studies identified the phenotype of a cardiomyocyte based on electrophysiological features of its action potential, the criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Analysis of the entire data set of APs (recorded across 32 hEBs) by an automated machine learning algorithm 47 divided the APs into different groups based on their shape and similarity to one another. This method also produced the most distinctive differences in AP waveforms between groups ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the entire data set of APs (recorded across 32 hEBs) by an automated machine learning algorithm 47 divided the APs into different groups based on their shape and similarity to one another. This method also produced the most distinctive differences in AP waveforms between groups ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PSC‐CMs themselves also pose a challenge to classification on this basis. While numerous reports have detailed the presence of nodal‐like, atrial‐like, and ventricular‐like APs in unguided differentiations of iPSC‐CMs , recent work by our group and others has shown that the AP morphologies of iPSC‐CMs do not robustly discriminate between multiple subpopulations of cells . While the question of whether different cell populations are present remains to be answered, if it is the case then they are not sufficiently distinct to be classified on the basis of their AP properties.…”
Section: Approaches To Assigning Chamber Typementioning
confidence: 92%
“…We were not the first to consider this weakness of work to date, with Gorospe et al (6) turning to computational methods to perform more quantitative comparisons of optically recorded AP waveforms with typical chamberlike morphologies, albeit in embryonic stem cell-derived cardiomyocytes. Tellingly, while this approach was able to distinguish a number of discrete AP phenotypes, this varied from just one to four or more distinct sets of morphologies depending on how the data was interpreted.…”
mentioning
confidence: 99%